Fuzzy theories and statistics—fuzzy data analysis. Issue 4 (2nd October 2021) - Watanabe, Norio
Abstract: Fuzzy theories are not well accepted in the field of statistics. However, fuzzy theories are important from the statistical viewpoint. In this note we first discuss the statistical applications of the fuzzy theories briefly. The main is the fuzzy set theory and we do not refer the fuzzy measure theory. Second, we introduce some statistical tools for analyzing fuzzy data. The fuzzy data analysis is important in the fields related to human sensitivity. Furthermore we define the fuzzy directional data as a special case of fuzzy data. The statistical analysis of fuzzy directional data is also discussed.